The influence of design and kinematic parameters of the knife on the specific cutting force of the sorghum-sudan hybrid - Ayugin N. P.; Semashkin N. I.; Romanov D. B.; Prikazchikov V. S.; Kalimullin M. N. (E3S Web of Conferences)
The paper presents results of the study on defining the specific cutting force of Nutritop Star sorghum-Sudan hybrid when changing kinematic and design parameters of the knife grinding device, such as: speed, sliding angle, sharpening angle, thickness and sharpness of the cutting edge of the knife. The knives with one-sided sharpening, comb and U-shaped knives were used in the laboratory studies. The research results can be used in design of cutting devices for choppers of plant materials, equipment for feed preparation, for combine harvesters when implementing the energy saving principle.